Propeller Flaps for Reconstruction around the Foot and Ankle - Teo, Tiew Chong (Journal of Reconstructive Microsurgery, 2020)
The propeller flap challenges conventional wisdom for the safe raising of flaps. Its unique design is based on a belief that a sizeable fasciocutaneous flap can be perfused by only a single perforator. What is more remarkable is the concept that this cleanly dissected pedicle can continue to safely perfuse the flap even when it is twisted 180 degrees. Clearly, meticulous technique is essential and the key points in raising this flap and its versatility for reconstruction of defects around the foot and ankle are discussed in this article.
Keywords: propeller flaps; perforator flaps; islanded local fasciocutaneous flap; dissection technique; lower limb reconstruction